Gambaran Dan Faktor Yang Memengaruhi Kepatuhan Konsumsi Tablet Tambah Darah Pada Siswi SMP Kota Banda Aceh - Auna Awalia; Iziddin Fadhil; Hady Maulanza (Lembaga Pengembangan Kinerja Dosen, 2023)
Adolescence is a stage between phase from childhood to adulthood, occurring between the ages of 10 and 19. During this period, teenagers require more nutrition, and one of the nutritional issues they face is anemia. Anemia is a condition where the number of red blood cells is below the normal threshold. Providing iron supplements in the form of blood-boosting tablets (TTD) is one technique to treat anemia in adolescents. The aims of this research is to understand the profile and factors influencing the level of compliance in consuming TTD among female junior high school students in Banda Aceh. The research follows an observational analytic approach with a cross-sectional design. It was conducted in several junior high schools in Banda Aceh (SMPN 1, SMPN 2, SMPN 3, SMPN 7, SMPN 8, SMPN 10, SMPN 12, SMPN 13, and SMPN 15) starting from July 2023. The sampling method used was cluster random sampling. Data collection involved distributing questionnaires and compliance cards directly to the female students. The data were evaluated using the statistical Chi-Square test. The research findings showed that out of a total of 108 female students, 40 respondents (64.5%) with good knowledge had regular TTD consumption. Additionally, 52 respondents (59.1%) with good behavior had regular TTD consumption. Based on the Chi-Square test with a significance level of 5%, the Chi-Square value for the relationship between knowledge and TTD consumption was (???? ???????????????????? = 0.005) < ???? = 0.05. Similarly, for the relationship between behavior and TTD consumption, the ???? value (P value = 0.006) < ???? = 0.05. The research's findings indicated thatthat knowledge and behavior significantly influence the level of compliance in TTD consumption among female junior high school students in Banda Aceh.